Escaping peril - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire, 2016)
When Peril leaves Jade Mountain Academy in order to find Queen Scarlet and destroy her before she can hurt Peril's friends, Peril must find a way to decide who she is really loyal to and what is most important.